Análisis de proyectos gestionados por educadores: el reto de la prevención del consumo de sustancias psicoactivas y violencia en jóvenes en Medellín (2012)
ABSTRACT: To analyze the development of projects formulated by professional teachers who are students of the certified course named “Red Formemos Educadores 2008-2010”. The projects were formulated in order to prevent violence and psychoactive drug use among the young students of Medellín, Colombia. Methodology: the Methodological elements proposed by grounded theory were used. Data collection was carried out in three stages: 1) one group interview, 2) four individual in-depth interviews, and 3) two individual in-depth interviews with two teachers and two interviews of the same nature with two members from the SURGIR NGO. No theories were formulated. Results: an important reason to develop prevention projects is the well-being of the young individuals living in communities where violence and drug use are common. Teacher motivation allowed for the successful development of the projects. Conversely, a lack of motivation led to withdrawal from the certified course. Discussion: the various problems of the teachers’ social environment have a direct effect on their motivations. For some teachers, the lack of time is an obstacle to carry out the academic activities proposed during the certified course. A motivated teacher can successfully face the difficulties encountered during the project development process.